Impact of Proactive Personality on Innovative Work Behavior and Task Performance: The Role of Work Engagement and Transformational Leadership in the Energy Industry Sector - Emerald Brilliant Kussoy; Mega Kurniawati DN; Justine Tanuwijaya (Budapest International Research and Critics University, 2022)
The relationship between proactive personality has a significant effect on IWB moderated by leadership style and employee engagement This study aims to examine whether leadership style has a direct effect on IWB. Tto facilitate the process of reviewing research results, the research design used was hypothesis testing, to test the effect of the independent variable, namely proactive personality, on the dependent variable, namely innovative work behavior. In addition, the mediating variable is job satisfaction and the moderating variable is transformational leadership. The data used in this research is cross sectional data on companies in the energy industry sector. In this study, it consists of 4 (four) variables, namely the independent variable or independent variable, the dependent variable or the dependent variable, and the mediating variable and moderating variable.